Integrated Pest Management for Florida Snap Beans - Ken Pernezny; Gregg Nuessly; William Stall (EDIS)
Integrated pest management (IPM) is a pest control strategy that uses a multitude of techniques to bring about effective, economic control of diseases, insects nematodes, and weeds in Florida snap bean fields. These techniques incude cultural methods, resistant varieties, biological control, and use of chemicals. This document is PPP 36, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date Revised: July, 2003.